2020
DOI: 10.1016/j.omtn.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from SIRT1-Overexpressing ADSCs Restore Cardiac Function by Improving Angiogenic Function of EPCs

Abstract: Acute myocardial infarction (AMI) is one of the leading causes of mortality in cardiovascular diseases. The aim of this study was to investigate whether exosomes from Sirtuin 1 ( SIRT1 )-overexpressing adipose-derived stem cells (ADSCs) had a protective effect on AMI. The expression of C-X-C chemokine receptor type 7 (CXCR7) was significantly downregulated in peripheral blood endothelial progenitor cells (EPCs) from AMI patients (AMI-EPCs) compared with that in healthy donors, which coin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 59 publications
2
25
0
Order By: Relevance
“…ASCs EVs could promote angiogenesis mainly via transferring functional microRNAs to targeted cells [ 19 , 56 , 85 , 103 , 122 , 168 , 169 , 173 , 177 , 180 , 181 ]. The underlying mechanisms for angiogenesis potential of ASCs EVs were shown as follows.…”
Section: Resultsmentioning
confidence: 99%
“…ASCs EVs could promote angiogenesis mainly via transferring functional microRNAs to targeted cells [ 19 , 56 , 85 , 103 , 122 , 168 , 169 , 173 , 177 , 180 , 181 ]. The underlying mechanisms for angiogenesis potential of ASCs EVs were shown as follows.…”
Section: Resultsmentioning
confidence: 99%
“…miR-21 in EnMSC-derived exosomes showed superior cardioprotection through angiogenic effects via the PTEN/Akt pathway [83]. Additionally, the exosomes from SIRT1-overexpressing ADSCs can help to restore the function of cell migration and tube formation and recruitment of EPCs to the repair area through the Nrf2/CXCL12/CXCR7 pathway [84]. Macrophage migration inhibitory factor engineered hUC-MSC-produced exosomes also significantly enhanced proliferation, migration, and angiogenesis by delivering miR-133a-3p to HUVEC [85].…”
Section: Myocardial Preservationmentioning
confidence: 99%
“…130 More recently, Huang et al applied exosomes derived from genetically modified ASCs to restore cardiac function through improving the angiogenic function of peripheral blood EPCs. 131 Indeed, the authors aimed to understand whether exosomes derived from silencing information regulator factor 1 (SIRT1) overexpressing ASCS (ASCs-SIRT1-Exos) may promote angiogenesis and myocardial repair of acute MI (AMI). The obtained results indicated that AMI could downregulate CXCR7 expression in EPCs and reduced their angiogenic function.…”
Section: Adipose-derived Stem Cellsmentioning
confidence: 99%